Does frequent tea consumption provide any benefit to cognitive function in older adults? Evidence from a national survey from China in 2018 - Wei, Chen; Zhang, Jiao; Chen, Na; Xu, Zhou; Tang, Huang (Frontiers in Public Health, 2023)
Objectives: This present study aims to investigate the effect of tea consumption on cognitive function and examine possible psychosocial mechanisms in older adults.The data of this study came from the 2018 wave of the Chinese Longitudinal Healthy Longevity Survey(CLHLS), and a total of 11,910 valid samples were included. We used ordinary least squares (OLS) to explore whether frequent tea consumption had significant effect on the cognitive function of older people. The problem of endogeneity was addressed by using a propensity score matching (PSM). Then we further explored the psychosocial mechanisms of the effect using a stepwise regression approach.Results: Frequent tea consumption produced a positive effect on Mini-Mental State Examination (MMSE) score (coefficient = 0.340, p < 0.01),and PSM showed similar results. Specifically, the positive effect of green tea (coefficient 0.409, p<0.01) was significantly greater than the other teas